Solitary spinal metastasis of renal cell carcinoma and en-bloc resection-A case report (Journal of Brain and Spine Foundation Nepal, 2020)
Renal Cell Carcinoma is a challenging condition for clinicians because of its poor response to radiotherapy, chemotherapy and even immunotherapy. Spine is the second most common site of metastasis and is also an indicator of poor prognosis. There is a significant dilemma for brain and spine surgeons about when to undergo aggressive surgical treatment, such as en-bloc resection of oligo-spine metastasis compared to conventional tumor excision by curettage. Here, we report a case of 60-year old female, a diagnosed case of renal cell carcinoma who had undergone right sided nephrectomy (with adrenalectomy) 5 years ago. She presented with history of pain over upper back. MRI revealed metastatic lesion over the thoracic T-7 vertebra. She underwent en-block total vertebral resection and reconstruction with titanium cage and pedicle screw fixation of the T-7 vertebra which healed with good results.